Fluorescence from graphene nanoribbons of well-defined structure - Zhao, S.; Rondin, Loic; Delport, Géraud; Voisin, C.; Beser, U.; Hu, Y.; Feng, Xinliang; Muellen, K.; Narita, Akimitsu; Campidelli, S.; Lauret, J. S. (Carbon, 2017)
Graphene nanoribbons synthesized by the bottom-up approach with optical energy gaps in the visible are investigated by means of optical spectroscopy. The optical absorption and fluorescence spectra of two graphene nanoribbons with different structures are reported as well as the life-time of the excited states. The possibility of the formation of excimer states in stacks of individual graphene nanoribbons is discussed in order to interpret the broad and highly Stokes-shifted luminescence lines observed on both structures. Finally, combined atomic force microscopy and confocal fluorescence measurements have been performed on small aggregates, showing the ability of graphene nanoribbons to emit light in the solid state. These observations open interesting perspectives for the use of graphene nanoribbons as near-infrared emitters.
CRIS-Team Scopus Importer:2023-03-20